2017
DOI: 10.1016/j.jspr.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of storage environment on the efficacy of hermetic storage bags

Abstract: Small hermetic bags (50 and 100 kg capacities) used by smallholder farmers in several African countries have proven to be a low-cost solution for preventing storage losses due to insects. The complexity of postharvest practices and the need for ideal drying conditions, especially in the Sub-Sahara, has led to questions about the efficacy of the hermetic bags for controlling spoilage by fungi and the potential for mycotoxin accumulation. This study compared the effects of environmental temperature and relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 39 publications
(51 reference statements)
2
34
0
1
Order By: Relevance
“…Similarly, Data logger placed inside the hermetic bags-PICS and woven polypropylene bag did not get fluctuate on its internal environmental profiles in two different locations and found no penetration of moisture too. (Lane & Woloshuk, 2017). …”
Section: Journal Of Maize Research and Developmentmentioning
confidence: 99%
“…Similarly, Data logger placed inside the hermetic bags-PICS and woven polypropylene bag did not get fluctuate on its internal environmental profiles in two different locations and found no penetration of moisture too. (Lane & Woloshuk, 2017). …”
Section: Journal Of Maize Research and Developmentmentioning
confidence: 99%
“…The current study stems from two previous studies in the United States and Kenya that examine the efficacy of storing maize in hermetic bags to reduce the risk of mycotoxin accumulation during storage. In both studies, maize was sealed in hermetic and woven bags and stored for 3 months at three locations, Indiana and Arkansas, United States, and Makueni County, Kenya ( Maina et al, 2016 , 2017 ; Lane and Woloshuk, 2017 ). Maize stored in the United States was harvested from a single source, while in Kenya individual farmers grew, dried and stored the maize at their farms.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature and relative humidity showed an increasing trend in all storage rooms from the start to the end of storage period. Although the optimum conditions for fungal spore germination and proliferation are different from those for mycotoxin production, temperature (15.8–34.9°C) and humidity (34.2%–89.7%) ranges in the study sites were in the intervals reported as suitable for both microbial growth (Choi et al, ; Garbaba, Diriba, Ocho, & Hensel, ; Lane & Woloshuk, ) and mycotoxin production (Choi et al, ; Lane & Woloshuk, ; Murphy, Hendrich, Landgren, & Bryant, ) in cereals including rice. The optimum temperature for the growth of Aspergillus spp.…”
Section: Resultsmentioning
confidence: 97%